Computeralization of Seaport Operation Management: Competitive Issues and Need of ICT Advancement - Bohari, Abdul Manaf (Information Management and Business Review, 2013)
In the perspective of seaport management, computeralization is the top priority issues as related on sustaining their operation and profitability. The dramatically change of global operation of seaport management with un-predictable situation has potential to exposed the seaport management with the major challenges where Information and Communication Technology (ICT) has play a vital role. In the one hand, ICT has potentially to bring the seaport management into the right way in order to face the current change of business environment. However, in the one hand, ICT has potential to brings risks, damage and any kind of negative impact to seaport operation if they miss-implement the suitable strategy to faced in the current practice of operation. As a fundamental of discussion, there are some current trends on seaport management issues will analyzed. The main objective of the paper is to discussed some current trends on competitive advantages issues that faced by seaport operation firms. Secondly, the paper is discussed the sophistication of Information and Communication Technology as used in the operation of seaport management. In the unpredictable business environment, ICT should integrate with seaport management strategy which can help the firms to strengthening their business in the global market position. Finally, some suggestion was made to guiding the seaport authority in integrating ICT sophistication with traditional management of seaport operation as alternatives way.